Non-GAAP earnings and stock price crash risk - HSU, Charles (Institutional Knowledge at Singapore Management University, 2022)
We investigate whether non-GAAP earnings disclosures increase stock price crash risk. Consistent with non-GAAP disclosures allowing managers to inflate investors' perceptions about firm performance, our results indicate that income increasing non-GAAP reporting increases crash risk. We also find that managers can use non-GAAP reporting as a substitute for earnings management to withhold bad news from investors (the traditional explanation for crashes). Finally, we find a positive association between non-GAAP reporting and the likelihood of subsequent events that can trigger a crash. Overall, our evidence is consistent with some non-GAAP disclosures exposing investors to risks of large and sudden price declines.(c) 2021 Elsevier B.V. All rights reserved.